2018
DOI: 10.1016/j.tet.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the asymmetric catalytic synthesis of chiral 3-hydroxy and 3-aminooxindoles and derivatives: Medicinally relevant compounds

Abstract: Several oxindole derivatives, of natural or synthetic origin, have been identified as medicinally appealing compounds, with a plethora of bioactivities reported. Chiral 3-hydroxy and 3-aminooxindole scaffolds have captured the attention of several research groups, due to their importance in drug discovery. In this review, we systematically address the wide variety of asymmetric catalytic methodologies employed in the preparation of these relevant chiral scaffolds, present in many biologically active compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 218 publications
0
19
0
Order By: Relevance
“…Squaramides (SQ) are derivatives of squaric acid (3,4-dihydroxycyclobut-3-ene-1,2-dione) that are widely used in a variety fields of expertise (Figure 1). They mostly dominate asymmetric synthesis as chiral ligands and H-bonding catalysts [24,25,26,27], but are also valuable building blocks in medicinal chemistry. Examples of small molecules with incorporated squaramide scaffold, that reached the various stage of clinical trials, are Perzinfotel (NMDA receptor antagonist) [28], and Navarixin (chemokine receptors 1 and 2 antagonist) [29] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Squaramides (SQ) are derivatives of squaric acid (3,4-dihydroxycyclobut-3-ene-1,2-dione) that are widely used in a variety fields of expertise (Figure 1). They mostly dominate asymmetric synthesis as chiral ligands and H-bonding catalysts [24,25,26,27], but are also valuable building blocks in medicinal chemistry. Examples of small molecules with incorporated squaramide scaffold, that reached the various stage of clinical trials, are Perzinfotel (NMDA receptor antagonist) [28], and Navarixin (chemokine receptors 1 and 2 antagonist) [29] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…When using [Ir(ppy) 2 (dtbbpy)]PF 6 , polar solvents such as DMF, DMSO, and MeOH showed relatively low compatibility compared with MeCN, giving the product in yields ranging from 40%-64% (entries 9-11). Only a trace amount of 2a was detected when less polar solvents were employed (entries [12][13][14]. Fortunately, we found that CF 3 CH 2 OH markedly improved the yield of this process to 88% (entry 15).…”
Section: Resultsmentioning
confidence: 87%
“…Consequently, their construction is of interest to organic chemists. Previously, several elegant methodologies were applied to build 3-substituted-3-hydroxy-2-oxindoles [10][11][12]. Transition metal catalyzed intramolecular cyclization of α-keto aromatic amides was reported to synthesize these versatile building blocks [13][14][15], and direct addition to isatin derivatives was also an efficient approach [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric synthesis of complex heterocyclic frameworks has always fascinated synthetic as well as medicinal chemists, looking at their wide occurrence in alkaloids, dyes, pharmaceuticals and agrochemicals. [1][2][3][4] Indole, among them, is considered as a privileged motif, owing to its occurrence in numerous molecules showing promising bio-activities such as anti-histamine, 5 anti-convulsant, 6 anti-microbial, 7 anti-tubercular, 8 anti-inammatory, 9 anti-diabetic, 10 anti-hypertensive, 11 anti-cancer 12,13 etc. (Fig.…”
Section: Introductionmentioning
confidence: 99%